Evaluation of Risk Factors and Cadmium in Patients During Hemodialysis (Medical Forum Monthly, 2024)
Objective: To evaluate the effectiveness of Hemodalysis for the heavy toxic metals.Study Design: Observational study.Place and Duration of Study: This study was conducted at the Institute of Biochemistry, Universitry of Sindh Jamshoro, Institute of M.A Kazi Chemistry, University of Sindh Jamshoro from August 2016 to February 2017.Materials and Methods: During this research work, 73 subjects of kidney dialysis treatment from three hospitals of Hyderabad city were studied. Patients were divided in three groups Diabetic Patients (DP) Kidney Patients (KP) and Hepatitis Patients (HP). Own prepared questionnaire were filled by patients at hospitals. Cadmium were analyzed from serum by Atomic Absorption.Results: 45.9% of subjects were founded Diabetic, 37.8% kidney failure patients and 16.3% were found Hepatitis patients. Number of male subjects was more affected than female. Vegetables, fruits and meat consumption was low in all groups. In this research work Cadmium were analyzed from before dialysis (Pre) and after dialysis (Post) samples. Mean±SD of cadmium in Diabetic Patients (DP), Kidney Patients (KP) and Hepatitis Patients (HP) was (1.17±0.15µg/L), (1.14±0.15 µg/l), (1.29±0.29 µg/l), (1.37±0.12 µg/l), (1.24±0.4 µg/l) and (1.14±0.10 µg/l) respectively.Conclusion: Besides other reasons, Diabetic Mellitus and Hepatitus have been main cause of Kidney failure, leading to Hemodialysis. Majority of Hemodailysis patients despite being Daibetic have been using soda drinks and tape water which can further aggravate or complicate their disorder and needed guidance and precautionary measure. No significant variations in Cadmium could be seen after hemodailysis therefore necessitating special attention on removal of heavy or toxic metals from blood by hemodialysis process.